A new mixed inhibitor of adenosine deaminase produced by endophytic Cochliobolus sp. from medicinal plant seeds - Zhang, Xin-Guo; Sun, Qiao-Yun; Tang, Peng; Ma, Guo-Yan; Guo, Guang-Jun; Guo, Si-Jia; Ma, Xiao-Di (Folia microbiologica, 2020)
Medicinal plants have been studied for potential endophytic interactions and numerous studies have provided evidence that seeds harbor diverse microbial communities, not only on their surfaces but also within the embryo. Adenosine deaminase (ADA) is known as a potential therapeutic target for the treatment of lymphoproliferative disorders and cancer. Therefore, in this study, 20 types of medicinal plant seeds were used to screen endophytic fungi with tissue homogenate and streak. In addition, 128 morphologically distinct endophyte strains were isolated and their ADA inhibitory activity determined by a spectrophotometric assay. The strain with the highest inhibitory activity was identified as Cochliobolus sp. Seven compounds were isolated from the strain using a chromatography method. Compound 3 showed the highest ADA inhibitory activity and was identified as 5-hydroxy-2-hydroxymethyl-4H-pyran-4-one, based on the results of 1H and 13C NMR spectroscopy. The results of molecular docking suggested that compound 3 binds to the active site and the nonspecific binding site of the ADA. Furthermore, we found that compound 3 is a mixed ADA inhibitor. These results indicate that endophytic strains are a promising source of ADA inhibitors and that compound 3 may be a superior source for use in the preparation of biologically active ADA inhibitor compounds used to treat cancer.
Keywords: semena rostlinná; ADA inhibitors; Plants, Medicinal; Seed endophytes; vazebná místa; Neoplasms; endofyty; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; adenosindeaminasa; Molecular Docking Simulation; inhibitory adenosindeaminasy; Seeds; simulace molekulového dockingu; Binding Sites; lidé; Humans; Adenosine Deaminase Inhibitors; Ascomycota; nádory; Adenosine Deaminase; Molecular docking; léčivé rostliny; Endophytes